The promise - Scott-Buccleuch, R. L. (Nxb. Đồng Nai, 2009)
When Kinsey Millhone’s landlord asks her to help deceased World War II vet Johnnie Lee’s family find out why the military has no record of his service, she thinks it’ll be a cinch. But she is about to meet her match in world-class prevaricators who take her for the ride of her life. When Lee’s apartment in burgled and a man named Ray Rawson, who claims to be an old friend of Lee’s, is beaten up, Kinsey soon finds herself on the trail of a pregnant woman with a duffel bag. Soon the intrepid P.I. is following leads halfway across the country and encountering another man from Lee’s past—a vengeful psychopath. Stalked by a new enemy and increasingly suspicious of Rawson—not to mention running out of time and money—now Kinsey must steer a collision course to solve a decades-old mystery that some would like better left unsolved.…